Avaliação do atendimento nos serviços de saúde à pessoa idosa - Lubenow , Juliana Almeida Marques (2016)
Introduction: The elderly are the most frequent users in health institutions and with increasing rate of life expectancy, the demand for these services tends to increase. Faced with this problem, health services need to be ready to offer care that meets the elderly needs. Objectives: discussing on access of older persons to primary health care services from an integrative review; evaluate the care for the elderly in healthy services (primary and specialized care services); and, identify the social representations of the elderly on the care in health services. Method: Exploratory research with mixed approach, supported by the Social Representations Theory, carried on with 266 elderly attended in Family Health Units and in the Integral Care for Elderly Health Center located in João Pessoa, Paraíba/Brasil. For data collection, an in-depth interview and an instrument with questions related to the care provided in the health services and socioeconomic and health data of respondents were used. Data were analysed with the SPSS package and IRaMuTeQ software and interpreted using the Social Representations Theory. Data collection took place between January and July 2015 after approval by the CEP/HULW Protocol 261/09 and CAAE: 0182.0.126.000-09. Results: Three articles were originated from this research: Access for the elderly to primary health care services: an integrative review; Health services care evaluation by the elderly; What elderly think about health services care. The elderly respondents mostly had between 60 and 69 years old, were female, with elementary school, married, family income of the two minimum wages, retired, lived with someone, they considered their health reasonable and showed a high prevalence of chronic diseases. In the Basic Health Units, access to health care is easier and the waiting time for care and transportation to the service was less than in the Specialized Care Center. In both services, elderly is always attended by the same physician, and in UBS they are also assisted by the same nurse. Most seniors considered organization, health professionals and staff punctuality, comfort and cleanliness excellent. About the social representations apprehended, the elderly associated good care to be treated with respect, care and education. For them, health professionals should talk, explain, show interest in their health problem and personal life. At the same time, they linked good care to medications and tests prescription, as well as referrals to specialists, strengthening the biomedical model of health care. Conclusion: The positive assessment of the services was represented by the elderly associated with well attended, despite the delay to be attended and to set appointments. It is recommended that elderly care in health services be centred in embracement practices in a humanized and qualified way, that meet their real needs, in which health professionals and managers need to consider the different characteristics of the elderly in their approach both in primary care and in the other levels of care.